Synthesis of Naphthylpyridines from Unsymmetrical Naphthylheptadiynes and the Configurational Stability of the Biaryl Axis - Fischer, Fabian; Siegle, Alexander Florian; Checinski, Marek; Fischer, Christine; Kral, Karolin; Thede, Richard; Trapp, Oliver; Hapke, Marko (The journal of organic chemistry, 2016)
A series of different unsymmetrically substituted naphthyl-based diynes were synthesized. These substrates formed the foundation for the assembly of novel biaryls containing pyridine moieties with differently substituted five-membered rings in the backbone of the newly formed heterobiaryl system. The key step for their efficient construction was the photo- and cobalt-catalyzed [2 + 2 + 2] cycloaddition reaction between the corresponding naphthyldiyne and aceto- or benzonitrile. The heterobiaryl products have been isolated and investigated with respect to the configurational stability of their biaryl axis using dynamic chiral HPLC; subtle effects of the substitution pattern on the stability of the axis were observed. For several compounds the activation barriers (ΔG‡) of racemization were determined. Suitable substitution of the five-membered ring backbone exemplarily allowed the Co-catalyzed enantioselective cyclization to yield the enantiomerically enriched heterobiaryl.
Gesehen am 19.05.2020